Investigating air temperature changes in Bhubaneswar city over 123 years from 1901 to 2023 - Abhipsa Das; Sarat Chandra Sahu; Roshan Beuria; Dipak Kumar Sahu; Artatrana Mishra; Amrutanshu Panigrahi; Abhilash Pati; Prajna Priyadarshini (Scientific Reports)
Abstract This study examines long-term air temperature trends in Bhubaneswar, a rapidly urbanizing coastal city in eastern India, using data from 1901 to 2023. By analyzing maximum, minimum, and mean temperatures, we assess both natural climate variability and anthropogenic influences, including urban expansion. Statistical techniques such as homogenization, persistence analysis, and low-pass filtering reveal a pronounced warming trend, particularly in minimum temperatures, as an indication of an intensifying urban heat island effect. A weak but positive correlation between minimum temperature and population growth supports the role of urbanization in shaping local climate. These findings contribute to understanding urban climate evolution in tropical coastal settings where natural and human factors interact. Our results underscore minimum temperatures compared to maximum temperatures, indicating a warming trend likely driven by anthropogenic activities. Regression analysis between population growth and minimum temperature affirms a weak but notable positive correlation, indicating the gradual intensification of Bhubaneswar’s local microclimate due to urban development. This study contributes to understanding climate dynamics in tropical, coastal, and urban regions, where natural and human factors converge, shaping distinct local climate patterns. Nonetheless, the climatic trends are less pronounced than the interannual fluctuations in temperature measurements. The little climatic differences across several generations are unlikely to have influenced human activities compared to the substantial impacts of interannual temperature variability.